Реактивный индукторный двигатель с аксиальным магнитным потоком - Рябов, Евгений Сергеевич (НТУ "ХПИ", 2010)
It is offered for direct drive to use a transverse flux reluctance motor which difference from axial flux motor is absence of constant magnets and formation of the electromagnetic moment only at the expense of change of conductivity of an air gap and degree of satiation of the magnetic system of motor. Expressions are resulted for the calculation of electromagnetic moment of motor
Keywords: безредукторный тяговый привод; гибридный привод; воздушный зазор; фазная катушка; каркас; магнитопровод